Composição e biogeografia da avifauna das ilhas Caviana e Mexiana, foz do Rio Amazonas - HENRIQUES, Luiza Magalli Pinto (Universidade Federal do Pará, 2013)
The islands of Caviana and Mexiana, located in the mouth of the Amazon River, are composed of fluvial sediments and well consolidated lands that date from the Terciary and that were separated from the continent by tectonic action at the beginning of the Holocene. The composition of the avifauna of these islands is analized both from the biogeographical and the ecological points of view. I registered 148 bird species for Caviana Island and 183 for Mexiana Island. The discrepancy between the size of the two islands (Caviana is larger than Mexiana) and the number of species observed is due to undersampling of Caviana. However, the analysis of faunal composition demonstrated that Caviana is richer in forest species than is Mexiana. In contrast, Mexiana showed a greater richness of birds of open habitats. These differences suggest that the rising of sea level at the beginning of the Holocene caused the extinction of greater part of the fauna of the understory ou Mexiana. The portions of Mexiana Island with "teso" vegetation were not submerged, maintaining their characteristic avifauna, which is also represented on Marajó Island. To analyse of the distribuitions of 157 species I subdivided the avifauna into seven categorias: widespread distribution in South America (77 species); widespread Amazonian distribution (25); distribution restricted to eastern Amazonia (7); distribution restricted to south of the Amazon River and east of the Tapajós River (3); distribution restricted to várzea (19); widespread distribution in northern Amazonia and absent from the Tocantins-Xingu interfluvium (5); and widespread distribution in Central Brasil (21). I did not find elements restricted to the Tocantins-Xingu interfluvium. This fact is related to ecological rather than historical factors. The pattern related to northern Amazonia can be interpreted as the result of recent dispersal, the system of islands at the mouth of the Amazon, or by the formation of the Purás and Gurupá Arches, which, associated with the lowering of sea level during Pleistocene, established a connection between lhe right and left banks of the Amazon River. The dispersal occurred in both directions, explaining lhe existence of a large number of species and subspecies with distributions restricted to eastern Amazonia, as well as the dispersal of Central Brasilian elements to north of the Amazon River. This last component of the avifauna is a1so related to the expansion of open vegetations, characteristic of Central Brazil, during glacial periods.